Caring for our youth: development and evaluation of a brief mindful self-compassion intervention for stress reduction and wellbeing promotion - Lim, Shu Hui Eunice (2016)
During the phase of emerging adulthood, youths are often faced with many internal and external stressors of life that they might find difficult to cope with, particularly the pressure to perform well in school. Exacerbated by overwhelming self-guilt when expectations are not met, youths can experience high stress levels and poor well-being. Prior research has demonstrated strong evidence in the effectiveness of mindfulness-based interventions like Mindfulness-Based Stress Reduction (MBSR), MBCT (Mindfulness-Based Cognitive Therapy) (MBCT) and Mindful Self-Compassion (MSC) interventions in reducing stress levels and improving well- being across various populations. In particular, a recent brief MSC intervention has lent strength for the efficacy of a short intervention among the undergraduate populations, though the same phenomenon has not been examined with Eastern populations. The present study thus aimed to develop and evaluate a brief 3-week MSC intervention that fosters self-care and well- being among Singaporeans. 30 NTU undergraduates were recruited to participate in the 3-week brief MSC intervention with data collected during pre-and-post intervention. Participants demonstrated improvements in self-compassion, self-esteem, empathy and reduction in perceived stress. No significant difference was found for hope. Findings suggested that the mindfulness mediation and self-compassion techniques imparted from the intervention cultivated greater self-acceptance and allowed undergraduates to embrace failures with unconditional kindness, thus reducing stress levels. Considering the short duration of the intervention, findings were encouraging and suggested a pivotal role that MSC interventions could play in empowering young people to better face the many challenges and adversities of everyday life. Keywords: mindfulness, self-compassion, self-esteem, perceived stress, empathic concern, hope